Improving medication adherence: A review of assessment methods and interventions - Aliaga, Lindita; Aliaga, Armend; Smilkov, Katarina; Naumovska, Zorica; Ackova, Darinka Gjorgieva (International Journal of Innovative Research and Scientific Studies, 2025)
The World Health Organization (WHO) defines adherence to medication treatment as "the extent to which the individual's behavior conforms to what is recommended in relation to treatment by the health care provider." Medication adherence continues to be a major challenge of medical treatment, with important implications for patient outcomes and the effectiveness of healthcare systems. Increased medication adherence has been associated with improved clinical outcomes, reduced costs to healthcare systems, and an improvement in the patient’s quality of life. On the other hand, non-adherence has been shown to lead to treatment failure, disease progression, as well as an increase in the number of hospitalizations. This review article analyzes the complex nature of medication adherence concerning assessment, intervention strategies, and related outcomes (including intention to treat). Adherence assessment methods include a range of methodologies, from self-reporting through electronic monitoring systems to the analysis of biochemical values. We discuss the advantages and disadvantages of these different methods, emphasizing the need for the implementation of validated instruments according to the patient's needs. Regarding improving medication adherence, multiple strategies need to be implemented. Maximizing adherence if, and where, feasible will reduce the disease burden of chronic illness, improve patient prognosis, and ultimately lead to more efficient healthcare. This review highlights the need to continually research and innovate in this critical area.